2022
DOI: 10.1136/bmj-2022-074093
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol related disorders among elite male football players in Sweden: nationwide cohort study

Abstract: Objectives To assess whether male elite football players are at increased risk of alcohol related disorders compared with men from the general population, and whether such an increased risk would vary on the basis of calendar year of the first playing season in the top tier of competition, age, career length, and goal scoring abilities. Design Nationwide cohort study. Setting Sweden, 1924-2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…We have previously found that elite football players in Sweden, when compared with general population men, have a lower risk of alcohol-related disorders and disorders related to other drug abuse, with the risk reduction being most pronounced in ages when the football player is typically active 32. Lower risk of alcohol and drug-related disorders, which have also been observed for former professional football players in Scotland,21 may protect against depression and anxiety-related disorders,33 although depression and anxiety-related disorders may also increase alcohol consumption 34.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that elite football players in Sweden, when compared with general population men, have a lower risk of alcohol-related disorders and disorders related to other drug abuse, with the risk reduction being most pronounced in ages when the football player is typically active 32. Lower risk of alcohol and drug-related disorders, which have also been observed for former professional football players in Scotland,21 may protect against depression and anxiety-related disorders,33 although depression and anxiety-related disorders may also increase alcohol consumption 34.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging literature using linked administrative health records has challenged this idea. In cohorts of Finnish contact sport athletes21 and professional Scottish18 and elite Swedish22 23 football players, athletes were shown to have no increased risk, and possibly even a reduced risk, of mood and substance use disorders as well as suicide relative to the general population.…”
Section: Introductionmentioning
confidence: 98%
“…Retired American footballers appear to have a higher prevalence of obesity and elevated blood pressure relative to the general population 6 but whether this observation is generalisable to other contact sports is uncertain. Indeed, erstwhile elite soccer players have a lower incidence of both alcohol-related disorders 7 and depression 8 at follow-up. Given the clear paucity of data on dementia risk factors in former contact sports participants, using general population controls as a comparator, we examined levels of nine dementia risk factors amongst retired elite boxers, wrestlers, and soccer players – all sports which have previously been linked to a higher burden of dementia.…”
Section: Introductionmentioning
confidence: 99%